The impact of diets rich in low-fat or full-fat dairy on glucose tolerance and its determinants: a randomized controlled trial - Schmidt, Kelsey A (Am J Clin Nutr, 2020)
BACKGROUND: Dairy foods, particularly yogurt, and plasma biomarkers of dairy fat intake are consistently inversely associated with incident type 2 diabetes. Yet, few trials assessing the impact of dairy on glucose homeostasis include fermented or full-fat dairy foods. OBJECTIVES: We aimed to compare the effects of diets rich in low-fat or full-fat milk, yogurt, and cheese on glucose tolerance and its determinants, with those of a limited dairy diet. METHODS: In this parallel-design randomized controlled trial, 72 participants with metabolic syndrome completed a 4-wk wash-in period, limiting dairy intake to ≤3 servings/wk of nonfat milk. Participants were then randomly assigned to either continue the limited dairy diet, or switch to a diet containing 3.3 servings/d of either low-fat or full-fat dairy for 12 wk. Outcome measures included glucose tolerance (area under the curve glucose during an oral-glucose-tolerance test), insulin sensitivity, pancreatic β-cell function, systemic inflammation, liver-fat content, and body weight and composition. RESULTS: In the per-protocol analysis (n = 67), we observed no intervention effect on glucose tolerance (P = 0.340). Both the low-fat and full-fat dairy diets decreased the Matsuda insulin sensitivity index (ISI) (means ± SDs −0.47 ± 1.07 and −0.25 ± 0.91, respectively) and as compared with the limited dairy group (0.00 ± 0.92) (P = 0.012 overall). Body weight also changed differentially (P = 0.006 overall), increasing on full-fat dairy (+1.0 kg; −0.2, 1.8 kg) compared with the limited dairy diet (−0.4 kg; −2.5, 0.7 kg), whereas the low-fat dairy diet (+0.3 kg; −1.1, 1.9 kg) was not significantly different from the other interventions. Intervention effects on the Matsuda ISI remained after adjusting for changes in adiposity. No intervention effects were detected for liver fat content or systemic inflammation. Findings in intent-to-treat analyses (n = 72) were consistent. CONCLUSIONS: Contrary to our hypothesis, neither dairy diet improved glucose tolerance in individuals with metabolic syndrome. Both dairy diets decreased insulin sensitivity through mechanisms largely unrelated to changes in key determinants of insulin sensitivity. This trial was registered at clinicaltrials.gov as NCT02663544.